SOCIAL SOLIDARITY IN THE DIGITAL AGE: CHALLENGES AND OPPORTUNITIES - Loso Judijanto; Rahmat Shodiqin; Aslan Aslan (Prosiding Seminar Nasional Indonesia, 2024)
Digital technologies have transformed the dynamics of social solidarity across the globe. This research examines this transformation in depth, taking into account the challenges and opportunities it creates. The literature review shows that cyberspace has a strong influence in strengthening the bonds of community across borders. Virtual communities of citizens have sprung up with ease, allowing cross-cultural interactions to take place more smoothly. Social networking sites facilitate collaboration and human connection on an unprecedented scale. However, digital porch technology has also created significant problems. One of the main issues relates to the risk of polarization due to automated filtration systems that tend to reinforce one-sided perspectives and "viewpoint overflow". Privacy of personal data and security of personal information are also serious issues, given the large volume of intimate data that users share on various online pages. Disparities in access to digital technology also remain a problem, leaving certain groups isolated from the times.